Vanadium Stress Alters Sweet Potato (Ipomoea batatas L.) Growth, ROS Accumulation, Antioxidant Defense System, Stomatal Traits, and Vanadium Uptake - Sunjeet Kumar; Mengzhao Wang; Yonghua Liu; Zhixin Zhu; Shah Fahad; Abdul Qayyum; Guopeng Zhu (MDPI AG, 2022)
Vanadium (V) is a heavy metal found in trace amounts in many plants and widely distributed in the soil. This study investigated the effects of vanadium concentrations on sweet potato growth, biomass, root morphology, photosynthesis, photosynthetic assimilation, antioxidant defense system, stomatal traits, and V accumulation. Sweet potato plants were grown hydroponically and treated with five levels of V (0, 10, 25, 50, and 75 mg L−1). After 7 days of treatment, V content at low concentration (10 mg L−1) enhanced the plant growth and biomass; in contrast, drastic effects were observed at 25, 50, and 75 mg L−1. Higher V concentrations negatively affect the relative water content, photosynthetic assimilation, photosynthesis, and root growth and reduce tolerance indices. The stomatal traits of sweet potato, such as stomatal length, width, pore length, and pore width, were also decreased under higher V application. Furthermore, V concentration and uptake in the roots were higher than in the shoots. In the same way, reactive oxygen species (ROS) production (hydrogen peroxide), lipid peroxidation (malondialdehyde), osmolytes, glutathione, and enzymes (catalase and superoxide dismutase) activities were increased significantly under V stress. In conclusion, V at a low level (10 mg L−1) enhanced sweet potato growth, and a higher level of V treatment (25, 50, and 75 mg L−1) had a deleterious impact on the growth, physiology, and biochemical mechanisms, as well as stomatal traits of sweet potato.